The Complete Letters of Henry James, 1887-1888 : Volume 1 - James, Henry, 1843-1916 (Book collections on Project MUSE., 2022)
"This first volume in The Complete Letters of Henry James, 1887-1888 contains 154 letters, of which 94 are published for the first time, written from early January to December 22, 1887. These letters mark Henry James's ongoing efforts to care for his sister, develop his work, strengthen his professional status, build friendships, engage timely political and economic issues, and maximize his income. James details work on "The Aspern Papers," Partial Portraits, and plans The Reverberator. This volume opens with James in the midst of a long sojourn in Italy and concludes with his inquiring about both the status of his essay to the American Copyright League and also the story "The Liar.""--